Pengaruh Variasi Media Pendingin Terhadap Kekerasan dan Mikrostruktur Pada Pengecoran Aluminium 6061 - Sigit Kristiadi; Unung Lesmanah; Artono Raharjo (RING ME, 2022)
The casting and the cooling process on the metal can affect the mechanical properties and physical properties that are formed. Changes in metal properties are influenced by the type and cooling medium in the metal cooling process. This study aims to determine the effect of different cooling media (Water, Dromus, and Coolant radiator) in the Quenching process on the hardness and microstructure of Aluminum 6061 which has passed the casting stage. It can be concluded that the variations in the cooling media used affect the different levels of hardness and microstructure of the test specimens. From the test results, it was found that the Water cooling media specimen had the highest level of hardness, the smallest grain size, and the amount of α-Al matrix formed was lower than the Dromus cooling media specimen. The test object with Dromus cooling medium has a higher hardness level, smaller grain size, and the amount of α-Al matrix formed is lower than the Coolant radiator coolant media test object which has the lowest hardness level, the largest grain size, and the amount of α-Al matrix the most